Hayek's market republicanism - Irving, Sean, author.
1 online resource (viii, 170 pages).
Keywords: "Friedrich Hayek was the 20th century's most significant free market theorist and over the course of his long career he maintained a sustained critique of the danger that state power poses to individual liberty. In rejecting much of the liberal tradition's concern for social justice and democratic participation, Hayek would help clear away many of the moral and intellectual obstacles to the emergence of neoliberalism in the last quarter of the 20th century. At the core of this book is a new interpretation of Hayek, painting him as an exponent of a neo-Roman conception of liberty and his work as a form of 'market republicanism'. It examines the contemporary context in which Hayek wrote, and places his work in a longer Western intellectual tradition. Hayek's Market Republicanism will be of interest to advanced students and researchers across the history of economic thought, the history of political thought, political economy and political philosophy"--